ANALISIS PENGGUNAAN TEKNIK KONSELING ONLINE UNTUK MEREDUKSI TINGKAT KECEMASAN MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR PADA MATA KULIAH KONSEP DASAR IPA - Marvinda Rizki Dita Dirgantara; Nurul Setiani; Usi Woro Minarsih; Wina Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore strategies for reducing student anxiety through online counselling techniques in the Basic Concepts of Science course. Data collection was conducted using questionnaires, observations, and interviews, with indicators focusing on learning independence (responsibility, self-confidence, initiative) and anxiety factors (academic stressors, interpersonal and intrapersonal stressors, teaching-related stressors, leisure time, community engagement, and personal time). The research employed a descriptive qualitative design with purposive sampling, involving six respondents categorized into low, moderate, and high anxiety levels. The findings revealed that students demonstrated behavioral improvements, with anxiety reduction observed by the ninth meeting. The counseling pattern implemented by lecturers included reflection, positive reinforcement, and opportunities for students to confront anxiety through presentations. These interventions fostered confidence and reduced stress responses. In conclusion, online counseling activities effectively reduced student anxiety in the Basic Concepts of Science course, supporting better engagement and performance in online learning environments.